Hacking exposed : unified communications and VoIP security secrets and solutions - Collier, Mark; Endler, David (New Delhi McGraw Hill Education, 2014)
"Establish a holistic security stance by learning to view your Internet telephony infrastructure through the eyes of the nefarious cyber-criminal. Hacking ExposedTM Unified Communications & VoIP, Second Edition offers thoroughly expanded coverage of today$1 (Bs rampant threats alongside ready-to-deploy countermeasures. Find out how to block TDoS, toll and social engineering fraud, service abuse, voice phishing, voice SPAM/SPIT, eavesdropping, and man-in-the-middle exploits. This comprehensive guide features all-new chapters, case studies, and examples"-- |c Provided by publisher.s
Machine generated contents note: 1 VoIP Components & Targets -- 2 Footprinting -- 3 Scanning & Enumeration -- 4 Toll Fraud & service Abuse -- 5 Harassing Callers & TdoS -- 6 Social Engineering & Information Harvesting -- 7 Voice Spam & Phishing -- 8 Infastructure Denial of Service -- 9 Network Eavesdropping -- 10 Interception -- 11 Cisco Unified Cisco Call Manager -- 12 Avaya Communication Manager -- 13 Microsoft Lync -- 14 Cloud, Emerging, and other Technologies -- 15 Fuzzing & Disrupting of Service -- 16 VoIP Signaling Manipulation -- 17 Audio & Video Manipulation.
Includes bibliographical references and index.
Keywords: Internet telephony -- Security measures; Computer networks -- Security measures